Enamel thickness and dental development in Rudapithecus hungaricus. Issue 136 (November 2019) - Smith, Tanya M.; Tafforeau, Paul; Pouech, Joane; Begun, David R.
Abstract: The fossil record of middle and late Miocene Eurasian hominoids has expanded considerably over the past few decades, particularly with the recovery of numerous isolated teeth and jaws. Scholars have turned to assessments of internal tooth structure and growth to make sense of the evolutionary radiations of these primates as well as their affinities to the living great apes (hominids). Here we characterize full-dentition enamel thickness and dental development in several juvenile Rudapithecus hungaricus individuals using multiple imaging modalities. Relative enamel thickness (RET) values for the anterior teeth and premolars of Rudapithecus are broadly akin to those of gorillas and chimpanzees and are thinner than those of orangutans. First molar RET values are most similar to chimpanzees, while posterior molar values are closer to thicker-enameled orangutans. When compared to Miocene hominoids, Rudapithecus shows an intermediate molar RET condition that is especially similar to other dryopithecines. Long-period line periodicity values are comparable to African apes and most Miocene hominoids, and lower than living and fossil orangutans. The mean cuspal daily secretion rate is similar to that of several other Miocene hominoids but is greater than extant great apes. Cusp-specific molar crown formation times generally exceed those of chimpanzees, are lower than those of orangutans, and are broadly like those of other Miocene apes. While Rudapithecus appears to have a somewhat unique pattern of enamel thickness and dental development relative to individual great ape genera, these structural and developmental features are consistent with its designation as a hominid.